2020
DOI: 10.1155/2020/1321283
|View full text |Cite
|
Sign up to set email alerts
|

Bone Defect Repair Using a Bone Substitute Supported by Mesenchymal Stem Cells Derived from the Umbilical Cord

Abstract: Objective. Bone defects or atrophy may arise as a consequence of injury, inflammation of various etiologies, and neoplastic or traumatic processes or as a result of surgical procedures. Sometimes the regeneration process of bone loss is impaired, significantly slowed down, or does not occur, e.g., in congenital defects. For the bone defect reconstruction, a piece of the removed bone from ala of ilium or bone transplantation from a decedent is used. Replacement of the autologous or allogenic source of the bone-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
(41 reference statements)
0
12
0
1
Order By: Relevance
“…Review of available literature supports the idea of using PL as a non-zoonotic adjuvant for cell culture in clinical research. It was proved that regeneration of bone and cartilage after application of MSCs combined with biomaterials takes place due to tissue replacement [44][45][46] . In case of neurological disorders, replacement mechanism of regeneration is disputable, however neuro-therapeutic potential of MSCs applied within hydrogel was observed due to their secretory properties, such as production of immunomodulatory or neurogenic factors 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Review of available literature supports the idea of using PL as a non-zoonotic adjuvant for cell culture in clinical research. It was proved that regeneration of bone and cartilage after application of MSCs combined with biomaterials takes place due to tissue replacement [44][45][46] . In case of neurological disorders, replacement mechanism of regeneration is disputable, however neuro-therapeutic potential of MSCs applied within hydrogel was observed due to their secretory properties, such as production of immunomodulatory or neurogenic factors 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The addition of MSCs to the composite biomaterial poly(3-hydroxybutyrate)/HA/alginate improves the regenerative potential, increasing bone formation in a critical-size defect by approximately four-fold [ 171 ]. Kosinski et al demonstrated the regeneration that occurred after 21 days of transplantation of umbilical cord derived MSCs seeded onto a scaffold of Geistlich Bio-Oss ® Collagen in a cranial defect [ 187 ]. Although their toxicity to eukaryotic cells is still under investigation [ 188 , 189 , 190 ], silver nanoparticles could promote the proliferation and osteogenesis of mesenchymal stem cells and improve femoral fracture healing when encapsulated in collagen and used at low concentrations [ 191 ].…”
Section: Bone Regeneration: Cellular Componentmentioning
confidence: 99%
“…BMP2, 4, 6, 7, and 9 have been reported to induce in vitro chondrogenesis of human MSCs [ 57 ]. UC-MSCs have been demonstrated to secrete BMP2 in vitro and to induce the increase of endogenous BMP4, 5, and 7 levels in vivo [ 58 60 ]. In addition, UC-MSCs induce overexpression of GDF5/BMP14/CDMP1, promoting chondrogenic differentiation in cocultures with fibroblast-like synoviocytes, thus, suggesting their potential in cartilage repair [ 61 ].…”
Section: Regeneration Mechanisms Of Uc-mscs For Cartilage Diseasesmentioning
confidence: 99%